Higuera Street, San Luis Obispo (1948)
View of businesses along Higuera Street at about the 700 Higuera block. Looking northeast. Riley's Department Store, Bank of America, Quality Meat Market, Dyer's Variety Store, Merle Norman Cosmetics, Maytag and Wedgewood. Standing at about 738 Higuera, Garden Street crosswalk visible.